Green Operations in Sports Facilities: A Review of Technological Implementation - Shariat Naseri, Aziz; Saffari, Leila; Majedi, Nima (AI and Tech in Behavioral and Social Sciences, 2025)
The increasing demand for sustainability in sports facilities has driven the adoption of green technologies aimed at reducing energy consumption, water usage, and waste generation. These technologies not only contribute to environmental conservation but also improve operational efficiency and reduce long-term costs for facility management. This article reviews the implementation of green technologies in sports facilities and assesses their impact on operational efficiency and sustainability. A comprehensive review of existing literature was conducted, focusing on renewable energy technologies, smart energy management systems, water conservation technologies, waste management innovations, and the use of sustainable materials in the construction and retrofitting of sports facilities. The review also explores the economic, technological, and operational challenges that affect the adoption of these technologies, as well as potential future directions for innovation and policy support. Green technologies, such as solar panels, smart HVAC systems, rainwater harvesting, and waste-to-energy solutions, have been shown to significantly reduce energy and water consumption while minimizing waste output. Despite the high initial costs, the long-term financial savings from reduced utility bills and maintenance costs make these technologies a valuable investment for sports facilities. However, barriers such as the high cost of installation, technological limitations in certain regions, and operational resistance present challenges to widespread adoption. The article highlights the importance of adopting green technologies in sports facilities to achieve both sustainability and operational efficiency. It calls for more research on scalable solutions and policy initiatives to encourage broader implementation, emphasizing the need for collaboration between facility managers, policymakers, and technology providers.